The identity of the largest enterprises located in Poland and communication of corporate social activities on corporate websites - Seiler Bartosz; Bortnowska Hanna (Management)
Today’s enterprises are becoming more and more socially active. In some respects, they are starting to resemble third-sector organizations. In the context of progressive isomorphism, the issue of organizational identity deserves attention. Identity is based, among others, on organizational mission and values, whose management requires the shaping of coherent links between these components, as well as actual efforts and their communication. Modern enterprises are markedly fond of using electronic media, including corporate websites, to communicate with the audience. The purpose of the article is to determine the prevalence of different types of missions and values among the largest enterprises located in Poland, especially those related to CSR, as well as to identify the relationship between their declared CSR missions and values and the presentation of selected corporate social activities on their corporate websites. It was found that two-thirds of the analyzed companies posted missions on their corporate websites. In most cases they declared focus on costumers, and less often - product superiority, innovation, or responsibility. Less than half of the companies presented organizational values through their websites. Those which prevailed are: professional, ethical, relational, and describing attitudes towards the environment. The analysis shows that every second analyzed company presented missions and values that referred to issues related to social responsibility. Enterprises that included references to responsibility towards the environment in their mission communicated only some of the corporate social activities. It was different in the case of enterprises which pointed to the importance of societal values among the declared values. Such organizations more often pursued CSR activities and communicated them. Therefore, it can be conclude that a better predictor of the effects of identity management in the area of CSR was the declaration of values related to social responsibility.